Factors Influencing Farmers’ Adoption of Climate Change Adaptation Practices : Evidence from Vietnam, Laos, and Cambodia - Fällström, Elice (SLU/Dept. of Economics, 2022)
Southeast Asia is among the most vulnerable regions to climate change, and its high dependence on agriculture imposes significant challenges on its farming systems. Given these challenges, farmers’ climate change adaptation is becoming increasingly important. Therefore, this thesis explored the interlinkages among – and the influence of – social support, knowledge, and various aspects of farmers’ perceptions on their adoption of climate change adaptation practices. Previous research in Southeast Asia has thus far focused on farmers’ attitudes towards – or barriers to – adaptation. This thesis goes a step further by providing insights into the underlying factors and how their interlinkages influence adaptation. Structural Equation Modelling was employed to account for the complexity of farmers’ adaptation behaviour. The results show that social support, knowledge, and perceived usefulness of adaptation practices have small positive direct effects on farmers’ adoption of adaptation practices. Perceived ease of use had a medium-sized positive direct effect, and also mediated the relationship between knowledge and adoption. Perceptions of climate change and its impacts were not found to have significant direct or indirect effects. The thesis concludes that perception should not be studied as a single latent construct when investigating Southeast Asian farmers’ adoption of adaptation practices but rather as multiple constructs. The findings contribute to the crucial research efforts needed in the region to understand how farmers’ adaptive capacity and food systems’ resilience can be strengthened. Thus, the findings also add to policy-relevant literature and provide a good foundation for future research on the development of climate change adaptation policies.